2018
DOI: 10.1016/j.ejca.2018.06.034
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes by line of therapy and programmed death ligand 1 expression in patients with advanced melanoma treated with pembrolizumab or ipilimumab in KEYNOTE-006: A randomised clinical trial

Abstract: NCT01866319.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
66
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(72 citation statements)
references
References 25 publications
4
66
0
2
Order By: Relevance
“…55,88 Post-hoc subanalyses after long-term follow up (median of 33.9 months) showed that compared with ipilimumab, pembrolizumab was associated with improvement in long-term PFS and OS for both patients who had received one prior systemic therapy and for those previously untreated. 89 Although initial reports of KEYNOTE-006 showed lower rates of treatment-related toxicities with pembrolizumab compared with ipilimumab, after long-term follow-up, the cumulative rates of treatment-related toxicities were similar across treatment arms. 33,55 Toxicity rates were higher with ipilimumab during the first 12 weeks of study treatment, but the frequency of new AEs tapered off after the completion of the ipilimumab regimen (which consisted of a maximum of 4 cycles) around 12 weeks.…”
Section: Ipilimumabmentioning
confidence: 94%
See 1 more Smart Citation
“…55,88 Post-hoc subanalyses after long-term follow up (median of 33.9 months) showed that compared with ipilimumab, pembrolizumab was associated with improvement in long-term PFS and OS for both patients who had received one prior systemic therapy and for those previously untreated. 89 Although initial reports of KEYNOTE-006 showed lower rates of treatment-related toxicities with pembrolizumab compared with ipilimumab, after long-term follow-up, the cumulative rates of treatment-related toxicities were similar across treatment arms. 33,55 Toxicity rates were higher with ipilimumab during the first 12 weeks of study treatment, but the frequency of new AEs tapered off after the completion of the ipilimumab regimen (which consisted of a maximum of 4 cycles) around 12 weeks.…”
Section: Ipilimumabmentioning
confidence: 94%
“…32,33,90,91 Long-term follow-up from several studies has shown that late responses to pembrolizumab can be observed more than a year after the start of treatment, and that initial PRs may become CRs with time. 32,33,69,89,91 A pooled analysis of cohorts from KEYNOTE-001 with long-term follow-up (median 43 months) showed that 16% of patients achieved CR, with median time to CR of 12 months, ranging from 3-36 months. 91 Across trials long-term follow-up has shown that responses to pembrolizumab are very long-lived, with median duration ranging from 23 months (2 mg/kg Q3W arm in Keynote-002) to much longer (eg, not reached even after 33.9 months follow-up in KEYNOTE-006).…”
Section: Ipilimumabmentioning
confidence: 99%
“…In addition, recently, Hamid et al [4] has reported the results of a case series with mucosal melanoma treated with pembrolizumab monotherapy. The objective response rate to pembrolizumab for ipilimumab therapy-naïve mucosal melanoma patients was 22%, suggesting a poor prognosis for mucosal melanoma compared to cutaneous melanoma patients [10]. Therefore, additional methods to enhance the anti-tumor effects of ICIs in patients with mucosal melanomas are needed.…”
Section: Discussionmentioning
confidence: 99%
“…However, the heterogeneity of tumor masses and the variety of antibodies available make it difficult to find such predictive biomarkers, and even PD-L1 expression might not be a promising marker. Collectively, many studies have suggested that PD-L1 expression on melanoma cells can represent a biomarker to test for the efficacy of anti-PD1 and related antibodies, such as Nivolumab, Ipilimumab, and Pembrolizumab [53][54][55], and other immune checkpoint inhibitors; however the PD-L1 expression is not always an effective marker for patients with cancer in other clinical trials [56,57]. For example, PD-L1 expression on melanoma cells in pretreatment tumor biopsy samples is reported to correlate with response rate, progression free survival, and overall survival in patients with advanced melanoma treated with anti-PD1 antibodies [55], but these antibodies are also effective for PD-L1-negative patients [57].…”
Section: Patients With Cancermentioning
confidence: 99%
“…treatment have been suggested, as above, there are still no common criteria of diagnosis. This fact limits the clinical usefulness of the diagnosis of PD-L1 expression, because the low sensitivity of immunohistochemical (IHC) assays using different antibody clones makes it difficult to establish staining platforms and scoring systems [54,55,[57][58][59]. To avoid misprediction by IHC staining, Conroy et al assessed the expression of PD-L1, using next-generation RNA sequencing, but the sensitivity of their system resembles that of IHC assay systems and is, in addition, more expensive [58].…”
Section: Patients With Cancermentioning
confidence: 99%